2021
DOI: 10.1016/j.conb.2020.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Posterior parietal cortex contributions to cross-modal brain plasticity upon sensory loss

Abstract: Highlights  The inferior posterior parietal cortex has a role in cross-modal plasticity  Age, social circumstances, attention and stress affect the posterior parietal cortex and crossmodal plasticity  Rehabilitation strategies for multimodal recovery or via functional implants should include the posterior parietal cortex

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 86 publications
1
6
0
Order By: Relevance
“…It may also occur later in life in older adults with age-related hearing loss who usually start developing hearing impairment in middle age (World Health Organization, 2021). With cross-modal plasticity, previous research suggested an inverse relationship between improved visual abilities and speech recognition (Glick and Sharma, 2017;Gilissen and Arckens, 2021). We also found that our dementia cohort tend to report lower speech recognition and understanding (Utoomprurkporn et al, 2021a).…”
Section: Possible Explanations For Improved Visuospatial Abilitysupporting
confidence: 76%
“…It may also occur later in life in older adults with age-related hearing loss who usually start developing hearing impairment in middle age (World Health Organization, 2021). With cross-modal plasticity, previous research suggested an inverse relationship between improved visual abilities and speech recognition (Glick and Sharma, 2017;Gilissen and Arckens, 2021). We also found that our dementia cohort tend to report lower speech recognition and understanding (Utoomprurkporn et al, 2021a).…”
Section: Possible Explanations For Improved Visuospatial Abilitysupporting
confidence: 76%
“…The neurobiological explanation for this phenomenon can be linked to the concept of sensory compensation and memory encoding [ 26 , 27 ]. Sensory compensation refers to the brain's ability to reorganize and enhance the processing of remaining sensory information when one sensory modality is compromised.…”
Section: Discussionmentioning
confidence: 99%
“…An fMRI study that presented movies to human participants reported that medial posterior parietal cortex (precuneus) accumulates information up to 12 s (Hasson et al, 2008). We argued that the long TRW allows the dmPPC to accumulate the continuous information of multifaceted representations from unimodal or integration of cross-modal inputs (Gilissen & Arckens, 2021) to support processing stream of past experiences for episode. This aligns with the higher temporal dynamics in the precuneus when remembering the unfolding of events that included a high density of experience units (Jeunehomme et al, 2022).…”
Section: Discussionmentioning
confidence: 99%